MAHABBAH DAN RUMANTIK PADA PASANGAN USILA - Purwari, Putri Intan; Murisal, Murisal (Universitas Islam Negeri Imam Bonjol Padang, 2019)
The purpose of this study is (1) to find out how the description of mahabbah and rumantik in the AN and M pairs (2) to find out what factors make the M and AN families can live in an atmosphere of mahabbah and rumantik, and (3) to find out how the process the M and AN families embody mahabbah and rumantik households.The method used in this study is a qualitative method with a case study model. Subjects consisted of 3 primary and secondary subjects. Data collection techniques through observation, interviews and documentation. The data analyst used the analysis of Miles & Huberman.The results of the study show that these elderly couples generally fulfill all aspects and indicators of mahabbah. As a supporting factor this couple can live in an atmosphere of mahabbah and rumantik are good at understanding their respective situations and conditions, mutual understanding, being honest, can correct themselves each, easy to forgive and is good at controlling emotions. The process embodies mahabbah and rumantik households that are equally trying between each other both in terms of the economy and the faithful of this couple.